2014
DOI: 10.1021/bi501443p
|View full text |Cite
|
Sign up to set email alerts
|

Membrane Defects Accelerate Outer Membrane β-Barrel Protein Folding

Abstract: Outer membrane β-barrel proteins spontaneously fold into lipid bilayers with rates of folding that are strongly influenced by the physical properties of the membrane. We show that folding is accelerated when the bilayer is at the phase transition temperature, because of the coexistence of lipid phase domains and the high degree of defects present at domain boundaries. These results are consistent with previous observations of faster folding into thin and highly curved membranes, which also contain a higher pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
68
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 53 publications
(70 citation statements)
references
References 24 publications
1
68
1
Order By: Relevance
“…Remarkably, EspP∆5 folded into proteoliposomes prepared with the gel phase lipid DPPC only slightly less efficiently than proteoliposomes prepared with the corresponding fluid phase lipid POPC. This is a striking result given that the folding of OMPs into pure gel phase liposomes has not been observed (25,28,32). We also found that EspP∆5 folded slightly less efficiently into proteoliposomes prepared with a mixture of POPC and POPE, POPG or CL than those prepared with POPC alone (Fig.…”
Section: The Bam Complex Catalyzes Efficient Folding Of Espp Into a Wmentioning
confidence: 52%
See 1 more Smart Citation
“…Remarkably, EspP∆5 folded into proteoliposomes prepared with the gel phase lipid DPPC only slightly less efficiently than proteoliposomes prepared with the corresponding fluid phase lipid POPC. This is a striking result given that the folding of OMPs into pure gel phase liposomes has not been observed (25,28,32). We also found that EspP∆5 folded slightly less efficiently into proteoliposomes prepared with a mixture of POPC and POPE, POPG or CL than those prepared with POPC alone (Fig.…”
Section: The Bam Complex Catalyzes Efficient Folding Of Espp Into a Wmentioning
confidence: 52%
“…Nevertheless, the results suggest that the ability of OMPs to fold is encoded within their amino acid sequence. The results also indicate that properties of lipid bilayers including fluidity (32,33), thickness (33), and head group charge or type (34) strongly affect the folding of many different β-barrel proteins. Although individual OMPs differ in their propensity to fold in different lipid environments (26,27), thin, fluidphase bilayers with charge-neutral lipid head groups (33) generally facilitate OMP folding, while naturally-occurring zwitterionic or negatively-charged lipid head groups inhibit or sometimes even preclude folding altogether (26).…”
mentioning
confidence: 86%
“…Reductions in temperature will also further decrease the fluidity of the characteristically rigid OM (15,16), which could exacerbate assembly defects of certain classes of proteins. The kinetics of OMP folding into a membrane is strongly influenced by the physical properties of the membrane, and temperature can strongly affect the biophysical properties of the OM, leading to changes in the rate of OMP folding with temperature (17)(18)(19)(20). Alternatively, or in addition, it seems likely that there is an increased requirement for periplasmic proteolysis in the BamA/BamD down mutant strains.…”
Section: Discussionmentioning
confidence: 99%
“…This process continues until the barrel is fully formed and membrane integrated. Such spontaneous folding can only occur in thin membranes made up by the short acyl chain lipids and at a temperature at or above phase transition, demonstrating the requirement of a membrane defect for an insertion (15). Native E. coli phospholipids, such as phosphoethanolamine (PE) and or phosphoglycerol (PG), do not support spontaneous OMP folding and hence a model was proposed that the Bam complex functions to reduce the kinetic barrier of membrane insertion by either creating a membrane defect and/or stabilizing certain transition conformations of the OMP at the membrane (28).…”
Section: Models For the β-Barrel Assemblymentioning
confidence: 99%